2020
DOI: 10.1007/s13555-020-00437-0
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis Among Adolescents in Kuwait and the Role of Siblings, Breastfeeding, and Household Cat and Secondhand Smoke Exposure: A Cross-Sectional Study

Abstract: Introduction: Globally, the epidemiology of psoriasis is poorly understood, and most countries lack essential epidemiologic data regarding disease burden and its determinants. This study sought to estimate the prevalence of psoriasis among adolescents in Kuwait and assess its association with different risk factors, including obesity, sibship size, breastfeeding, and exposure to household secondhand smoke (SHS) and pets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…4 The frequency of positive FH of psoriasis ranges from 6.7% to 57.7% in various countries outside Japan. 6,[8][9][10][11][12][13] Although older studies showed a wider range (2.0%-90.9%) of positive FH of psoriasis, 14,15 extreme high and low frequency are uncommon. Farber et al collected data on the frequency of FH of psoriasis from all over the world and found that 11.0% of Japanese patients with psoriasis had FH of psoriasis in 1971.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The frequency of positive FH of psoriasis ranges from 6.7% to 57.7% in various countries outside Japan. 6,[8][9][10][11][12][13] Although older studies showed a wider range (2.0%-90.9%) of positive FH of psoriasis, 14,15 extreme high and low frequency are uncommon. Farber et al collected data on the frequency of FH of psoriasis from all over the world and found that 11.0% of Japanese patients with psoriasis had FH of psoriasis in 1971.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriatic arthritis (PsA) is another condition with a strong genetic predisposition 4 . The frequency of positive FH of psoriasis ranges from 6.7% to 57.7% in various countries outside Japan 6,8–13 . Although older studies showed a wider range (2.0%–90.9%) of positive FH of psoriasis, 14,15 extreme high and low frequency are uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…The earliest study showed that almost half of the married couples in Kuwait were consanguineous (11), and the most recent one showed a little decline but still indicated a high number of consanguinity at 46% (10). Some research studies recently reviewed the relationship between consanguinity and increased rate of certain inherited genetic disorders in Kuwait, which include mitochondrial diseases (12)(13), inborn errors of immunity (14)(15), classic homocystinuria, congenital malformations (16-17), primary ciliary dyskinesia (18), retinitis pigmentosa (19), and hyperoxaluria type 1 (20).…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis is a chronic systemic inflammatory disease. The global age-standardized prevalence of psoriasis is 0.84% 1 ; however, the prevalence of psoriasis in the Gulf Cooperation Council countries tends to be higher, approaching 5.3% in the Kingdom of Saudi Arabia, [2][3] 3.6% in the State of Kuwait, 4 and 1.6% in the Sultanate of Oman. 5 A strong association exists between metabolic syndrome and psoriasis.…”
Section: Introductionmentioning
confidence: 99%